Шедевры искусства 20 века: альбом / перевод с английского Е. С. Гордон - Гордон Е. С. (АСТ-ЛТД, 1997)
Экземпляры: ЦБ (2002 г.) / Инвентарный номер: 35879 / Цена: 86.90 / Авт.знак: Ш 38 / ГРНТИ: 18 / ББК: 85